Study on Surface Esterification of Cellulose Nanocrystals Their and Lipid-Lowering Effect - Jiachuan Yang; Jianxia Liu; Xiaochen Zhang (Journal of Natural Fibers)
With the rapid development of the economy and changes in dietary structure, there is an excessive intake of high sugar and high-fat foods. To address this issue, in this study, we grafted palmitic acid onto CNC in the form of ester groups and evaluated its adsorption performance. Research had found that among these three methods, the CDI catalytic method can successfully obtain esterification modified CNC while also taking into account its environmentally friendly and pollution-free characteristics. Compared with CNC, its adsorption capacity for oil had increased, with the maximum adsorption capacity increasing from 35.80 g/g to 46.91 g/g. Meanwhile, the degree of esterification substitution of esterification modified CNC was measured, and the result was 0.03. Especially, after adding CNC-PA, the hydrolysis of fat was significantly reduced during the simulated digestion in vitro, whilst the absorption of fat in the intestine was significantly inhibited. In vivo testing also confirmed that consuming a diet containing CNC-PA significantly reduced elevated levels of triglycerides (TG) compared to the high-fat control group while long-term feeding of a diet containing CNC-PA reduced weight and fat accumulation.